Pengujian Black Box Menggunakan Metode Equivelence Partitions dan State Transition Pada Aplikasi Angrem RSUD Campurdarat - Muhammad Taufikurrohman; Ilyas Nuryasin (LPPM STIKI MALANG, 2024)
Application testing is important to ensure that the application can function properly without any bugs or errors from the application system. In this study, testing of the Angrem RSUD Campurdarat application needs to be done to ensure that the application can function properly without any bugs or errors when the application is used. This test uses two methods of black box testing, namely equivalence partitions and state transitions. The use of these two methods is necessary because they have different focuses. Equivalence partitions test the data input section from the user while state transitions test the flow or transition of the application. Equivalence partitions testing divides the input space into several partitions so that it can reduce the number of test cases. Based on the research that has been conducted on the Angrem RSUD Campurdarat application using the equivalence partitions and state transition methods, the test results show quite good application performance with some parts that need improvement. The results obtained are that in the equivalence partitions method from 44 test cases, there are 37 successful test cases and 7 failed test cases while in the state transition method there are 16 page transitions tested and all tests in this method are successful.